KARAKTERISTIK PENDERITA SIROSIS HATI RAWAT INAP DI RSUD DR PIRNGADI MEDAN TAHUN 2010-2011 - stiphany marpaung (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Liver cirrhosis is one of the diseases found throughout the country. In the world (2004) liver cirrhosis was ranked eigthth leading cause of death with prevalence 1,3%. In Indonesia (2004) liver cirrhosis ASDR reached 13.9 per 100,000 population. This research is to know the characteristics of inpatient care in hospital Dr. Pirngadi Medan in 2010-2011, with descriptive case series design. Total population are 103 people and sample are all patients liver cirrhosis who are hospitalized of 103 people (total sampling). Patients with the highest proportion in the age group 49-55 years (28.2%), male gender (68.9%), Islam (64.1%), Batak tribe (57.3%), high school education (67%), job self-employed (40.8%), residence / place of origin of Medan (59.2%), abdominal bloating (44.7%), classification dekompesanta cirrhosis (95.1%), history of previous illness that other liver diseases (25.2%), complication status are no complications (52.4%), type of complication is esophageal varices and bleeding (55.1%), the source of the cost is Askes (41.7%), length of treatment on average 9.31 days and coming home is the home state of ambulatory (72.8%). From the statistic analysis, there were no significant differences between the sexes based on classification of cirrhosis (p=0,627), and length of treatment on average with this type of complication (p=0,373). There are significant differences between the average treatment time is based on sources of cost (p=0,016), maintainability and long on average based on the state of coming home (p=0,000). Recommended to the Hospital Dr.Pirngadi Medan to provide more intensive treatment for patients with liver cirrhosis, especially with complications.   Keywords: Liver Cirrhosis, The Characteristic of Patients